Effect of Mycorrhizal Inoculation and Frequency of Watering to The Seedling Growth of Agarwood (Aquilaria malacensis, Lamk) - Gloria E Patty; Johan M Matinahoru; Miranda H Hadijah (Tropical Small Island Agriculture Management, 2022)
Currently, many farmers have been trying to cultivate agarwood plants, after various studies have produced fungi that can be infected to agarwood plants to produce gaharu sap. However, the propagation of agarwood plants until now still has several inhibiting factors, especially problems with soil fertility and optimal water availability for seedling growth. Controlling soil fertility using synthetic fertilizers is no longer recommended due to pollution problems, so efforts towards using biological fertilizers are now the focus of utilization. Therefore, this study aimed to determine the effect of mycorrhizal fungus inoculation and frequency of watering on the growth of agarwood seedlings in nurseries with the growth parameters, namely: increase in plant height, stem diameter, number of leaves and percentage of mycorrhizal fungal infections in agarwood seedling roots. The research results showed that the treatment between mycorrhizal inoculation (I1) and the frequency of watering every 2 days (A2) resulted in good average growth of agarwood seedlings. This is because the highest mycorrhizal fungal infection, which is 93.3%, occurred in the treatment of the combination between mycorrhizal inoculation and the frequency of watering in every 2 days. The highest agarwood seedling was 25.70 cm, obtained from a variety of treatment between mycorrhiza inoculation and the frequency of watering in every 2 days. Meanwhile, the treatments without mycorrhizal inoculation at all levels of frequency of watering resulted low growth rates of agarwood seedlings.